Body weight and eating attitudes influence improvement of depressive symptoms in children and pre-adolescents with eating disorders: a prospective multicenter cohort study - Yuichi Suzuki; Shinichiro Nagamitsu; Nobuoki Eshima; Takeshi Inoue; Ryoko Otani; Ryoichi Sakuta; Toshiyuki Iguchi; Ryuta Ishii; Soh Uchida; Ayumi Okada; Shinji Kitayama; Kenshi Koyanagi; et al. (BMC Pediatrics, 2024)
Abstract Background Pediatric patients with eating disorders in a multicenter joint study on 11 facilities were enrolled and prospectively investigated to determine whether improvement in body weight, eating attitudes, and psychosocial factors in children with eating disorders would also improve depressive symptoms. Methods In this study, 91 patients were enrolled between April 2014 and March 2016. The severity of underweight was assessed using the body mass index-standard deviation score (BMI-SDS), eating behavior was assessed using the children's eating attitude test (ChEAT26), the outcome of childhood eating disorders was assessed using the childhood eating disorder outcome scale, and depressive symptoms were assessed using the Children's Depression Inventory (CDI) score. Results After 12 months of treatment, depressive symptoms were evaluated in 62 of the 91 cases where it was evaluated at the initial phase. There was no difference in background characteristics between the included patients and the 29 patients who dropped out. A paired-sample t-test revealed a significant decrease in CDI scores after 12 months of treatment (p < 0.001, 95% CI: 2.401–7.373) and a significant increase in the BMI-SDS (p < 0.001, 95% CI: − 2.41973–1.45321). Multiple regression analysis revealed that BMI-SDS and ChEAT26 scores at the initial phase were beneficial in CDI recovery. In addition, BMI-SDS at the initial phase was useful for predicting BMI-SDS recovery after 12 months of treatment. Conclusions Depressive symptoms in children with eating disorders improved with therapeutic intervention on body weight and eating attitudes. Trial registration The Clinical Trial Number for this study is UMIN000055004.